Evaluation of healing of varicose ulcers after endovenous laser ablation of great saphenous vein - Mohamed, Hatem Hussein; Alshahat, Beshoy Magdy; Almezaien, Mamdouh Mohamed (International Surgery Journal, 2020)
Background: Varicose veins are permanently swollen, tortuous and elongated while standing due to back flow of blood caused by incompetent valve closure which result in venous congestion .they are of two types primary and secondary varicosities .The main symptoms are tingling, itching, pain, fatigue, a heavy feeling in the legs especially if one has to stand for a long time. Ulcers and thrombophlebitis are possible complications. The aim of this study is to assess the outcome of laser ablation of great saphenous vein on healing of varicose ulcers. Methods: A prospective study conducted at Suez Canal University Hospitals and Nasser Institute Hospital in Cairo on 20 patients complaining varicose ulcers due to incompetent saphenous femoral junction. Results: All patients had improvement in Abrdeen Varicose vein questionnaire after endovenous laser ablation (EVLA) during the first, second and third follow up visits when compared with preoperative scores. The Aberdeen Varicose vein questionnaire ranged from 8 to 18 before the procedure, with a mean of 12.11, ranged from 3 to 11 at the first follow up visit with a mean of 7.07, ranged from 2 to 10 at the second follow up visit with a mean of 4.89 and ranged from 2 to 10 at the third follow up visit with a mean of 3.85, p value is less than 0.001 compared to the pre-operative data. During the assessment of the patients of our study after 6 months of continuous follow up, we found that the healing rate of the patients who underwent laser ablation of great saphenous vein were (91.67) (p=0.769). Conclusions: EVLA of great saphenous vein leads to better wound healing rates in treating patients with varicose ulcers.